Usabilidade e acessibilidade no Repositório de Informação Acessível da UFRN: avaliação ergonômica de interfaces Web - Furtado, Margareth Maciel Figueiredo Dias (2016)
This research aims to evaluate the ergonomic requirements of usability and accessibility present in the Accessible Information Repository interface, based on the opinion of users with low vision and blindness. The implementation of this overall goal was given by the following specific objectives: a) check functionality of buttons and links in the Accessible Information Repository interface of Federal University of Rio Grande do Norte, b) identify obstacles and inconsistencies in the interface usability and accessibility, c) know the points liable to improvements in the Accessible Information Repository interface that contribute with subsidies to the elaboration of intervention proposal to be held at the Federal University of Rio Grande do Norte. The research is characterized as exploratory, descriptive and applied, using the methodological strategy of case study, based on a quantitative and qualitative approach. Data collection was made with the development of usability testing, participant observation and semi-open questionnaire. For quantitative analysis of the data was used the statistical method; and for the qualitative analysis was used content analysis. For the convergence of the results it used the triangulation of data for multiple instruments. The sample studied was composed of eight registered users in the Accessible Information Repository, representing 25 % of this population. As for the characterization of the participants, the analysis showed the following profile: women (50%), between 31 and 40 years, three with low vision and one with blindness, being three undergraduate and one a graduate student; men (50%), between 34 and 53 years, all with blindness, two undergraduate and two graduate students. The results showed points with necessity of changes in the interface repository. Identification of points of obstacles to the functions: descriptive captions and inadequate size of buttons and icons, such as contrast buttons, site map and start and end session buttons; lack of functionality in the map of the site and shortcuts, as well as lack of a return function. It was also found that regardless of obstacles, participants applied other measures to complete the tests. As for the registration recommendations, we highlight the need for descriptive caption, increase of icons size, activation of inactive links, implementation of new features and periodic technical evaluation. The survey also proved that the participants conceived the identification of inconsistencies and suggestions for improvements as enhancement factor for the interface, confirming that the condition of the site at the time of the test was considered acceptable. It is considered that due to constant changes in technologies and possible demands of the actual and potential users of the repository, it will be required new evaluations in the future to confirm the quality of service.